PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI SISWA MENGGUNAKAN METODE GUIDED WRITING DI KELAS IV SDN 01 BATANG ANAI KABUPATEN PADANG PARIAMAN - Septiani, Melsy; Sukma, Elfia; M.Habibi; Putri Zulkarnaini, Aissy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low narrative text writing skills of fourth-grade students of SDN 01 Batang Anai, Padang Pariaman Regency. Students have difficulty in finding ideas, arranging a series of events coherently, and using appropriate linguistic elements. In addition, teacher guidance in the writing process is not optimal so that student learning outcomes are still low. This study aims to describe the improvement of students' narrative text writing skills through the application of the Guided Writing method in fourth-grade students of SDN 01 Batang Anai, Padang Pariaman Regency. This type of research is Classroom Action Research (CAR) with a qualitative and quantitative approach implemented in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The research subjects consisted of the class teacher as observer, the researcher as practitioner, and 26 students of class IV.A. Data were collected through observation, tests, and non-tests, then analyzed qualitatively and quantitatively. The results of the study indicate that the application of the Guided Writing method is able to improve the quality of learning and students' narrative text writing skills. The percentage of learning planning increased from 88% to 96%, the implementation of learning in the teacher aspect from 89.28% to 96.42%, the student aspect from 85.71% to 96.42%, while the average student writing skills increased from 81.11 to 86.71. Thus, the Guided Writing method is effective in improving the narrative text writing skills of fourth grade students of SDN 01 Batang Anai, Padang Pariaman Regency.